O conceito de sustentabilidade nas políticas de desenvolvimento territorial no Brasil - Magalhães, Daniel (2012)
Despite the adjective \'sustainable\' follows almost all public policies in Brazil, in most cases, there is no explicit definition of the sustainability concept used. This dissertation deals, in the second chapter, with the institutionalization of sustainable development concept and the incorporation of the environmental issues in economic theory. We discuss in this work different concepts of sustainability in economic theory, giving priority to neoclassical and ecological economics. The third chapter discusses the evidence that space has acquired in development policies and recommendations by the multilateral development agencies, who started to prescribe the endogenous development aproach. In the last part of the third chapter, we discussed the territorial cohesion concept, which take sustainability as essential for the harmonious territory development, with natural resources, biodiversity and environmental services protection. The fourth chapter shows the first territorial experiences in Brazil and an analysis of sustainability concept in development policies of the Agrarian Development and the Social Development Ministries. Finally, we test the heterogeneity of the sustainability concet in territorial development policies of these ministries.